Molecular detection of bovine alphaherpesvirus 1 and 5 in the brain of cattle with and without neurological disease - Júlio Augusto Naylor Lisbôa; José Renato Junqueira Borges; Lilian Azevedo Figueiredo; Gustavo Rodrigues Queiroz; Rodrigo Azambuja Machado de Oliveira; Bruna Stephani Ribeiro; Janildo Ludolf Reis Junior; Márcio Botelho de Castro; Selwyn Arlington Headley; Amauri Alcindo Alfieri (Semina: Ciências Agrárias)
The objective of the present study was to verify the presence of DNA of bovine alphaherpesvirus 5 (BoAHV5) and 1 (BoAHV1) in brain samples from healthy cattle slaughtered or that died naturally affected by neurological diseases. The healthy ones were beef cattle (n=30) raised in the north central mesoregion from Paraná, southern Brazil. The sick cattle had a definite diagnosis of rabies (n=38), BoAHV encephalitis (n=25) and other neurological diseases (n=37). Polymerase chain reaction (PCR) assays were performed on fragments of the telencephalon, cerebellum and brain stem to confirm the presence of BoAHV5 and BoAHV1 DNA. Bovine alphaherpesviruses were confirmed in cases of BoAHV5 (n=22) and BoAHV1 (n=3) encephalitis. There were no observed coinfections. In rabid cattle, BoAHV5 was confirmed in eight (21%) and BoAHV1 in one (2.6%). BoAHV5 was also present in two (5.4%) cattle with other diseases (botulism and polioencephalomalacia), and in two (6.6%) healthy cattle. It can be concluded that, due to the possibility of latent infection, the presence of BoAHV5 or BoAHV1 DNA in the brain of cattle that died with neurological diseases may complicate the differential diagnosis in some cases.